Franklin bifocal, a solution for prismatic correction of paralytic strabismus - Bolduc, M; Gresset, J (Canadian Journal of Optometry, 2021)
A Franklin bifocal gives one the possibility of doing a sector prism to replace a Fresnel prism in cases of paralytic strabismus. Thus, visual acuity and the aesthetic aspect of the equipment can be enhanced.